2023
DOI: 10.3390/ma16093317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasma Treatment on Surface Characteristics of Aluminum Alloy Sheets and Bonding Performance of Glass Fiber-Reinforced Thermoplastic/Al Composites

Abstract: This study focuses on modifying the surface of an AA 5052-H32 aluminum alloy using plasma treatment. Discharge power, exposure time, and working gas were adjusted as process parameters to improve the adhesion between the aluminum alloy and glass fiber-reinforced thermoplastic (GFRTP) polycarbonate composite. The surface composition and morphology of the aluminum alloy sheet were analyzed by X-ray photoelectron spectroscopy and scanning electron microscopy, and surface roughness and wettability were evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The results showed that the interlaminar shear strengths of FMLs were significantly enhanced due to the formation of TiO2 nanotube arrays on the surface of titanium sheets FMLs. Tsai et al [11] modified surfaces of aluminum alloy using nitrogen plasma treatment, leading to a 25% increase in the bonding strength between aluminum alloy and GFRTP. Zhang et al [12] carried out the treatment of magnesium alloy surface with a phosphating solution before manufacturing the fiber metal laminate based on magnesium (MgFML).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the interlaminar shear strengths of FMLs were significantly enhanced due to the formation of TiO2 nanotube arrays on the surface of titanium sheets FMLs. Tsai et al [11] modified surfaces of aluminum alloy using nitrogen plasma treatment, leading to a 25% increase in the bonding strength between aluminum alloy and GFRTP. Zhang et al [12] carried out the treatment of magnesium alloy surface with a phosphating solution before manufacturing the fiber metal laminate based on magnesium (MgFML).…”
Section: Introductionmentioning
confidence: 99%
“…the values for tensile strength, flexural strength, and shear strength are 362.52 MPa, 474.25 MPa, and 54.63 MPa, respectively. The final comprehensive performance score of the FMLs can becalculated using Eq(11).…”
mentioning
confidence: 99%